FOOD SAFETY AND HYGIENE CONDITIONS IN SELECTED PUBLIC SECONDARY SCHOOLS WITH BOARDING FACILITIES IN IBADAN, NIGERIA (2013)
Cases of food contamination and poisoning in boarding schools have been reported in Nigeria. Although researches have been carried out on food safety in Nigerian schools, not many studies were conducted in boarding schools despite the health implications of consuming unsafe food. This study was designed to assess the food safety and hygiene conditions in selected Public Secondary Schools with Boarding Facilities(PSSBF) in Ibadan, Nigeria. Stratified random sampling technique was used to select five out of ten PSSBF in Ibadan. A semi-structured interviewer administered questionnaire was used to elicit information on Knowledge, Attitude and Practice (KAP) of food safety and hygiene among 59 food handlers. A 40, 24 and 30 point scales was used to assess the food handlers KAP respectively. Food hazards and sanitary conditions were assessed by direct observation using a 30-item checklist. Forty-two food samples were collected immediately after cooking from kitchens and dining halls of schools. Food holding temperature was measured by inserting thermocouple in the mid region of the food samples. Borehole, well and Tap water samples used for dish-washing, cooking and drinking were collected from the schools. Food and water samples were assessed for bacteria using pour plate and multiple tube method and results expressed in cfu/g and cfu/ml respectively. Values obtained from analysis of food and water samples were compared with United States Food and Drug Administration (USFDA) and Standard Organization of Nigeria (SON) respectively. Descriptive statistics, Chi-square test, t-test and ANOVA were used for data analysis at p=0.05 Mean age of food handlers was 34.5±10.1 years. Mean Knowledge Attitude and Practice scores on food safety was 26.9±4.9, 13.4±3.2 and 21.9±3.8 respectively. Objects observed in food sampled were artificial finger nails, drug capsules, and tiny metals. Toilet facilities in the schools were in poor sanitary conditions with no running water. The mean temperature at holding for food samples in oC were: rice (57.4±4.6), “moi-moi” (57.1±5.9), “akamu” (34.3±1.5), vegetable-soup (59.0±6.7) and yam-porridge (63.4±3.6). There was a significant difference between temperature at holding for all food compared to the USFDA standard. The types and loads of bacteria isolated from the food samples were Escherichia coli (4.4x108), fecal coliform (5.1×108), Staphylococcus aureus (1.2x108) and Bacillus cereus (8.4x108) cfu/g. These were significantly higher than USFDA standard for food safety. Mean total coliform of 18 and 16cfu/100ml were obtained for cooking and drinking water respectively. Total coliform for cooking and drinking water exceeded SON water safety level. The level of food and water contamination in the schools was high. Although the food handlers have average knowledge of food safety and hygiene, the hygiene condition of food surroundings and toilets was poor. Therefore, there is need for hygiene education, training on food safety and regular monitoring in boarding secondary schools.